Evolução da Iniquidade educativa no ensino básico de Portugal. Eficácia das políticas educativas implementadas (Revista Lusófona de Educação, 2025)
Over the past 25 years, Portugal has stood out for promoting significant educational policies aimed at improving the quality of its system. Given that, the evidence suggests these initiatives successfully increased the academic performance levels of students in the third cycle of basic education and secondary education during the early years of the 21st century, this study seeks to analyze whether improvements are also observed in educational equity levels. PISA databases for Portugal were used to derive indicators of inequality and segregation at both the student and school levels. Despite initially obtaining unfavorable results in the early PISA assessments, the findings show how educational inequality levels between schools have evolved positively in Portugal, reaching more favorable levels in recent years compared to neighboring countries. A deeper analysis suggests a causal relationship between the evolution of equity levels and the implementation of educational policies in the country. These results are valuable for guiding new policy proposals in education aimed at promoting social justice.